Should weight-bearing activity be reduced during healing of plantar diabetic foot ulcers, even when using appropriate offloading devices?. (May 2021) - Jarl, Gustav; van Netten, Jaap J.; Lazzarini, Peter A.; Crews, Ryan T.; Najafi, Bijan; Mueller, Michael J.
Highlights: It is debated if weight-bearing activity in offloading devices delays ulcer healing. Weak evidence exists for an inverse relationship between activity and healing. We propose a Diabetic foot Offloading and Activity framework for future research. Abstract: Physical activity is an essential part of general health and diabetes management. However, recommending weight-bearing physical activity for people with plantar diabetic foot ulcers is controversial, even when gold standard offloading devices are used, as it is commonly thought to delay healing. We aimed to narratively review relevant studies investigating the relationship between plantar diabetic foot ulcer healing and weight-bearing activity, plantar pressure and device adherence. We defined relevant studies as those from two systematic reviews, along with those identified since using a similar updated Pubmed search strategy. We identified six studies. One study found that more daily steps were associated with worse ulcer healing, three found no significant association between steps and ulcer healing, and in two others the association was unclear. Thus, there is weak evidence for an inverse relationship between weight-bearing physical activity and plantar ulcer healing while utilizing offloading devices. We propose a Diabetic foot Offloading and Activity framework to guide future research to find the optimal balance between the positive and negative effects of weight-bearing activity in the context of foot ulcers. We hope such future studies will shed more conclusive light on the impact of weight-bearing activity on healing of plantar diabetic foot ulcers.